EVALUASI SURVEILANS COVID-19 DI PUSKESMAS BULELENG I KABUPATEN BULELENG - Ni Luh Putu Seri Wardani; I Nyoman Purnawan; Made Nyandra (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
This research has the aim to evaluate aspects of COVID-19 surveillance input in Buleleng Health Center I. The research design used is descriptive research with qualitative approach. Data collection techniques used are in-depth interview techniques with research informants as many as 5 people with purposive sampling techniques and data retrieval techniques using structured interviews, documentation studies and observations. The conclusion of this study is that man is not in accordance with the guidelines; methode in accordance with the guidelines is the availability of guidelines for prevention and prevention of COVID-19 Disease Rev.5; the allocation of funds has not been in accordance with the guidelines because the amount of funds available does not match the increase in cases that occur but the source of funds is appropriate; facilities and infrastructure are only problems of the internet network that have not been in accordance with the guidelines